2022
DOI: 10.3390/heritage5040198
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is a Buddhist Pilgrimage Circuit as a Product and Strategy for Heritage Tourism in India?

Abstract: Buddhist heritage in India is receiving reasonable attention for tourism development with a particular emphasis on promoting Buddhist circuits. One Buddhist pilgrimage circuit covering eight locations including four most sacred places, namely, Bodhgaya, Sarnath, Kushinagar, and Lumbini, is popular for spiritual and religious reasons. Fieldwork conducted in these four sites reveals complex patterns of visitation that question the idea of a circuit as a tourism product. The primary circuit-goers are foreign Budd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, it is also important to consider that pilgrims are there for spiritual experiences. Overexposed tourism products and services may add recreational value, but on the other hand, they may be disruptive [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to consider that pilgrims are there for spiritual experiences. Overexposed tourism products and services may add recreational value, but on the other hand, they may be disruptive [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits that can be obtained from heritage tourism depend on several factors-not only the attractiveness of the place, customs, historical, or sentimental values, but also the involvement of all stakeholders in the tourism area. For example, research on the effectiveness of pilgrimage tourism has shown that itineraries depend on several factors, including travel convenience, accommodation options, ability to perform pilgrimage rituals, and institutional management for tourism [22]. Managers of cultural heritage sites need to remember to ensure authenticity, culinary appeal, atmosphere, and quality of service [23].…”
Section: Heritage Tourism Functionsmentioning
confidence: 99%
“…The timeline of the establishment of different Buddhist monasteries shows that the growth of Sarnath as a Buddhist pilgrimage center has been sluggish, compared to other places such as Bodhgaya, which presently boasts of more than 200 monasteries of varying sizes [7]. In terms of attractions, the Thai monastery and its gardens are the most visited because of their close vicinity to the archaeological ruins.…”
Section: Sacred Geographymentioning
confidence: 99%
“…As such, alongside Bodhgaya (where the Buddha attained Enlightenment), Lumbini (where the Buddha was born), and Kushinagar (where the Buddha died), Sarnath is considered one of the most sacred sites by Buddhists on a Buddhist pilgrimage circuit in India. While both Bodhgaya and Lumbini are renowned Buddhist pilgrimage centers that are listed as WHSs and attract millions of visitors, the same cannot be said of Sarnath and Kushinagar [7]. This paper aims to examine the trajectory of Sarnath's development as a Buddhist pilgrimage center and what could being listed as a WHS means for its future.…”
Section: Introductionmentioning
confidence: 99%